State‐Level Determinants of Hate Crime Reporting: Examining the Impact of Structural and Social Movement Influences. (31st January 2020) - Scheuerman, Heather L.; Parris, Christie L.; Faupel, Alison H.; Werum, Regina
Abstract : In this article, we investigate factors affecting hate crime policies by examining anti‐LGBT (lesbian, gay, bisexual, transgender) hate crime reports as a type of policy implementation. Analyzing state‐level data drawn primarily from the US Census between 1995 and 2008, we examine how structural and social movement mobilization factors explain hate crime reporting. We find that anti‐LGBT hate crimes are more likely to be reported in more urbanized states and in states with both split political elites and a greater number of LGBT social movement organizations. We discuss the implications of our findings for separating the drivers of policy passage from policy implementation and for complementary criminological and social movement explanations for hate crime reporting.